THERMAL SIMULATION OF THE CZOCHRALSKI PROCESS FOR SILICON CRYSTAL GROWTH USING FINITE ELEMENT MODELING APPROACH - Nugroho, Willy Satrio; Alamsyah, Fikrul Akbar; Chanampa, Carlos Nicolas Quispe (International Journal of Mechanical Engineering Technologies and Applications, 2024)
This study investigates the thermal dynamics of the Czochralski (CZ) process for silicon crystal growth through numerical simulations. The simulation method of this study is based on finite element method (FEM) heat transfer simulation. The FEM simulation was performed using triangular mesh in half cross section of CZ system with real material properties. The analysis of heat transfer mechanisms includes conduction, convection, and radiation which reflect the impact of cooled argon convection on crystal growth. The simulations reveal that convection currents driven by cooled argon has a crucial role to promote uniform cooling which control crystal growth. This leads to enhanced mono-crystalline silicon ingot crystal quality and purity. Ultimately, insights gained from this study can inform optimization efforts in semiconductor manufacturing, facilitating advancements in electronic device fabrication.